2008
DOI: 10.1166/jbns.2008.033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <I>In-Vitro</I> Analysis of Degradative Resistance of a Novel Bioactive Composite

Abstract: The biostability of the polymer is one of the critical parameter to use them for biomaterial application. Polyurethane being one of the most compliant polymer but there are concerns regarding its resistance to degradation, particularly from hydrolysis and oxidation. The aim of this study is to synthesise a novel bioactive composite by creating a covalent linkage between polyurethane and nano-apatites and to analyse the in-vitro hydrolytic degradation of a series of newly synthesised polyurethane (PU) and polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…The concept of creating mechanically/chemically homogenous units “ideal monoblocks” with root dentin is challenging. Our previous studies, confirmed the biostability of newly developed nanocomposite,15 the results of thermal properties, in vitro bioactivity, adhesion with root dentin were presented in subsequent studies 16,17. The incorporation of nHA in these composites enhanced the bioactive properties, thermal stability, and increased the resistance toward hydrolytical degradation.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The concept of creating mechanically/chemically homogenous units “ideal monoblocks” with root dentin is challenging. Our previous studies, confirmed the biostability of newly developed nanocomposite,15 the results of thermal properties, in vitro bioactivity, adhesion with root dentin were presented in subsequent studies 16,17. The incorporation of nHA in these composites enhanced the bioactive properties, thermal stability, and increased the resistance toward hydrolytical degradation.…”
Section: Introductionsupporting
confidence: 71%
“…The general concept of cell interaction demonstrates that cells attach much more readily to hydrophilic materials than to hydrophobic surface. The hydrophilic/hydrophobic nature of this novel material was previously analyzed by contact angle measurement 15. The degree of contact angle allows characterizing the surface wettability of a material, and can act as an indicator of its hydrophilicity/hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been previously reported that by adding nano-HA as a filler, the material then becomes unsuitable for clinical performance and is hydrolytically unstable as compared to composites with microscopic particles 86,87) . The hydrophilicity of HA is due to the presence of the -OH group in its hexagonal structure that can easily attract surface moisture 153) , however it can be addressed with surface grafting during in situ synthesis 154) .…”
Section: Ha-based Dental Resinsmentioning
confidence: 99%
“…Fillers need silanization to immobilize them in the resinous matrix 5) . Previously, our group showed that addition of n-HA in the polymeric network and, on the other hand, the presence of hydrophobic matrices increased the degree of wetting and reduced water sorption 4,25,26) . In the current study, addition of n-HA improved the polymerization process.…”
Section: Discussionmentioning
confidence: 98%